Peningkatan Produktivitas Lansia Di Panti Wreda Widhi Asih Surakarta Melalui Sekar Panik (Senam, Karya, Pangan, Hidroponik) Berbasis Active Ageing - vadesma, iwanda; Rajagukguk, Aranssa Dwiveronikca; Aprilia, Nadia; Setiawan, Irvan; Setyomurti, Mikha Anggitama; Rahadhini, Marjam Desma (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
Elderly people are those who have reached the age of 60 years or more who need activities to avoid experiencing dementia, the elderly have socio-psychological problems related to stress, loneliness and mental problems. So the PKM-PM team at Slamet Riyadi University, Surakarta, provided an activity to make the elderly productive through skills activities at the Widhi Asih Nursing Home, Surakarta. The methods applied in this activity include: (1) providing information related to the skills activities carried out (2) preparing the main materials and skills framework, (3) making craft skills from plastic spoons, used cardboard and flannel, (4) process final completion of skills and monitoring with the elderly. The result of the service is that seniors are able to participate in craft skills activities from start to finish with enthusiasm. Skills activities can fill the elderly's free time thereby suppressing dementia. Activities can be developed with creativity, new skills according to the abilities and desires of the elderly. This service has achieved the expected results and the sustainability of this program continues to be carried out through monitoring pattern.